The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/scan/nsz060
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HTTLPR polymorphism impacts moral permissibility of impersonal harmful behaviors

Abstract: Inspired by the roles of serotonin in an emotional aversion to harmful actions, we examined to what extent serotonin transporter gene (5-HTT)–linked polymorphic region (5-HTTLPR), a proxy for measuring serotonin function, underpinned the individual differences in moral judgment through cross-sectional analysis and two-wave comparison. The cross-sectional analysis with a larger cohort (N = 1197) showed that the SS carriers of the 5-HTTLPR polymorphism, corresponding to the low ratio of serotonin recycling from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Hence, there is a 9.27% decrease in the participants' willingness to answer positively to perform an action that would have as an outcome harm or death (even when such harm or death is in the end inevitable) to another person, as a function of a one increase in S alleles being carried. effects of the 5-HTT gene, which has also been found to be associated with anxiety, morality, and even cultural structures (Fergusson et al, 2011;Mrazek et al, 2013;Perkins et al, 2013;Yang et al, 2019). While anxiety was found to be significantly associated with the permissibility to harm, the direction of such correlation was opposite, depending on the emotional valence and moral justification behind the harmful behaviors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hence, there is a 9.27% decrease in the participants' willingness to answer positively to perform an action that would have as an outcome harm or death (even when such harm or death is in the end inevitable) to another person, as a function of a one increase in S alleles being carried. effects of the 5-HTT gene, which has also been found to be associated with anxiety, morality, and even cultural structures (Fergusson et al, 2011;Mrazek et al, 2013;Perkins et al, 2013;Yang et al, 2019). While anxiety was found to be significantly associated with the permissibility to harm, the direction of such correlation was opposite, depending on the emotional valence and moral justification behind the harmful behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…This would help us tackle the well-known and widely debated argument of affect versus cognition in regard to moral decision-making. Given the impact of the “epigenetic” mechanisms that encode environmental information from both internal and external bodily sources, a single genotype–phenotype linkage cannot be established without simultaneously considering the multifaceted effects of the 5-HTT gene, which has also been found to be associated with anxiety, morality, and even cultural structures ( Fergusson et al, 2011 ; Mrazek et al, 2013 ; Perkins et al, 2013 ; Yang et al, 2019 ). While anxiety was found to be significantly associated with the permissibility to harm, the direction of such correlation was opposite, depending on the emotional valence and moral justification behind the harmful behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies have extensively investigated the genetic foundations of moral behaviors. For instance, the OXTR rs63576, COMT Val158Met, and 5‐HTTLPR have be found to be associated with bystanders' acceptability for harmful actions (Gong, Fang, Yang et al ., 2017; Marsh, Crowe, Yu, Gorodetsky, Goldman & Blair, 2011; Ru, Fang, Wang et al ., 2017; Walter, Montag, Markett, Felten, Voigt & Reuter, 2012; Yang, Wang, Li et al ., 2019). However, there are significant differences in the moral emotions between bystanders and victims.…”
Section: Introductionmentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) is a protein involving in the differentiation and survival of neurons. Studies indicated that the expression of BDNF in the brain is regulated by oxytocin and serotonin transporter (Benedetti, Ambree, Locatelli et al ., 2017; Chang, Lee, Chi et al ., 2018; Zhang, Shahrokh, Hellstrom et al ., 2020), both of which are related to moral acceptability (Walter et al ., 2012; Yang et al ., 2019). The BDNF Val66Met (i.e., rs6265), a non‐synonymous single‐nucleotide polymorphism (SNP), produces an amino acid change from valine (Val) to methionine (Met) at codon 66 in the BDNF gene.…”
Section: Introductionmentioning
confidence: 99%